Effectiveness of papaya seed (Carica papaya L) solution against fungal prevalence and hatching power of koi carp (Cyprinus carpio L) eggs - Sarifudin Sarifudin; Nasmia Nasmia (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
One of the causes of the low production of koi carp seeds is fungal attack during the egg-hatching period, so natural treatments need to be carried out, including the use of papaya seeds. Papaya seeds contain antifungal compounds in the form of tannins, flavonoids, saponins, and alkaloids. The purpose of this study was to determine the effective dose of papaya seed solution in reducing the prevalence of the fungus and increasing the hatchability of koi goldfish eggs. This study was designed using a completely randomized design, which consisted of 5 treatments with 4 replications each. The treatment tested was papaya seed solution with treatment doses A=control, B=125 mg L-1, C=150 mg L-1, D=175 mgL-1, and E=200 mg L-1. Variables measured included the prevalence of the fungus, egg hatchability, observation of the fungus, hatching time, and water quality. The results showed that treatment with 125 mg L-1 of papaya seed solution reduced the prevalence of the fungus by 32.5% and resulted in the highest egg hatchability of 67.5%. The high hatchability of eggs is due to the presence of antifungal compounds in the form of flavonoids, saponins, tannins, and karpain contained in papaya seeds which provide protection for eggs against fungal infections so that eggs can hatch properly. The best dose of papaya seed solution to prevent fungal infection in koi carp eggs obtained at 200 mg L-1, 11.25%.